A new species and two new record species of genus Allokepon Markham, 1982 (Isopoda: Epicaridea: Bopyridae) from China - Duan, Jiangyan; An, Jianmei; Yu, Haiyan (Zootaxa, 2008)
Descriptions of a new species and two new records of species of the genus Allokepon Markham, 1982 from Chinese waters are presented. The host species were portunid crabs. Allokepon hendersoni (Giard & Bonnier 1887) was found infesting Charybdis bimaculata (Miers), A. monodi (Bourdon, 1967) infesting Portunus pelagicus (L), Portunus trituberculatus (Miers), and Thalamita sp. and A. longicauda n. sp. infesting Portunus pulchricristatus (Gorden). Three of the host species were recorded for the first time harboring isopod parasites, and the male of A. monodi is presented. Allokepon longicauda n. sp. is distinguished from the other four species found in China by the long slender uropods of females.